PENERAPAN FUNGSI KURVA BAHU DAN SEGITIGA PADA METODE FUZZY SUGENO DALAM MENENTUKAN KELAYAKAN KONSUMEN DALAM MEMBELI PROPERTI - Ema Wardiana; Rismayanti; Dharmawati (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2020)
Marketing is the spearhead in a company, whether it is engaged in services or products. One of the most important assets owned by a company in its efforts to maintain its viability,developing, the ability to compete and earn a profit. Therefore, marketing must minimize the possibility of offering products to targets that are not potential. Application of the decision support system for determining the target market by using the Sugeno fuzzy method aims to minimize potential targets. Based on the tests carried out, it can be seen that the representation of the membership function of the shoulder curve and triangle curve can produce the expected decisions. This application is built by using the C # programming language which is implemented by Visual Studio 2010 ands designed by unity 3D software.